Impaired anti-fibrotic effect of bone marrow-derived mesenchymal stem cell in a mouse model of pulmonary paracoccidioidomycosis. - Julián Camilo Arango; Juan David Puerta-Arias; Paula Andrea Pino-Tamayo; Lina María Salazar-Peláez; Mauricio Rojas; Ángel González (Public Library of Science (PLoS), 2017)
Bone marrow-derived mesenchymal stem cells (BMMSCs) have been consider as a promising therapy in fibrotic diseases. Experimental models suggest that BMMSCs may be used as an alternative therapy to treat chemical- or physical-induced pulmonary fibrosis. We investigated the anti-fibrotic potential of BMMSCs in an experimental model of lung fibrosis by infection with Paracoccidioides brasiliensis. BMMSCs were isolated and purified from BALB/c mice using standardized methods. BALB/c male mice were inoculated by intranasal infection of 1.5x106 P. brasiliensis yeasts. Then, 1x106 BMMSCs were administered intra venous at 8th week post-infection (p.i.). An additional group of mice was treated with itraconazole (ITC) two weeks before BMMSCs administration. Animals were sacrificed at 12th week p.i. Histopathological examination, fibrocytes counts, soluble collagen and fibrosis-related genes expression in lungs were evaluated. Additionally, human fibroblasts were treated with homogenized lung supernatants (HLS) to determine induction of collagen expression. Histological analysis showed an increase of granulomatous inflammatory areas in BMMSCs-treated mice. A significant increase of fibrocytes count, soluble collagen and collagen-3α1, TGF-β3, MMP-8 and MMP-15 genes expression were also observed in those mice. Interestingly, when combined therapy BMMSCs/ITC was used there is a decrease of TIMP-1 and MMP-13 gene expression in infected mice. Finally, human fibroblasts stimulated with HLS from infected and BMMSCs-transplanted mice showed a higher expression of collagen I. In conclusion, our findings indicate that late infusion of BMMSCs into mice infected with P. brasiliensis does not have any anti-fibrotic effect; possibly because their interaction with the fungus promotes collagen expression and tissue remodeling.